Offender rehabilitation in Hong Kong: current practice and service development - Wong, Aaron H. L. (Approaches to offender rehabilitation in Asian jurisdictions, 2024)
As one of the safest cities in the world, Hong Kong has very low crime and recidivism rates. These successes are partly attributable to the authorities’ efforts in promoting offender rehabilitation. This chapter explores Hong Kong's rehabilitation services in prisons, youth correctional institutions, drug addiction treatment centres, a psychiatric centre, and in the community. The correctional services in Hong Kong provide education, work and vocational training, and psychological services to spark offenders’ inner motivation to change and live a law-abiding life. The chapter also discusses how Hong Kong's offender assessment and treatment programmes incorporate elements of the Risk-Need-Responsivity and Good Lives Models. Finally, the chapter suggests future research directions to better evaluate the effectiveness of Hong Kong's rehabilitation approach.